Predictors of public support for the death penalty in the Americas: A comparative analysis - Boateng, Francis D. (Criminology & criminal justice, 2025)
The primary purpose of this study was to explore public support for capital punishment in seven Latin and North American countries to determine factors that influence citizens’ support for the death penalty. Currently, most of the countries examined in the study do not have death penalty for ordinary crimes, but do have it for cases involving murder, war crimes, genocides, terrorism, and crimes against humanity. Our analysis made several important observations that enhance our understanding of citizens’ attitudes toward the death penalty in the Americas. For instance, we found that a significant majority of citizens from the countries under review support the death penalty even though it currently does not exist in practice. With regard to factors, we found that nationality, religiosity, prior experience with victimization, residential stability, quality of life, life satisfaction, age, and gender were among the factors that heavily predict support for the death penalty in this part of the world. The findings of this study have serious implications for research and practice.